"Sticks and Stones May Break My Bones but Words Will Never Hurt Me": Ageing, Invisibility and Textual Play. Issue 3 (2nd September 2017) - Handler, Sophie
ABSTRACT: Based on the work of Ageing Facilities (an informal age-focused research platform), this article looks at how the tactics of disrupting the language around ageing can start to generate a critically reflective and situated dialogue around the subject of ageing – a subject still marginalized within architecture and design. In writing about ageing in different ways, this article argues, it becomes possible to rethink dominant modes of engaging with the subject of ageing. Looking at a specific text piece (an alternative dictionary of age-related terms), this article examines the working mechanics of these textual tactics. These are tactics, it is argued, that by drawing on a tradition of textual experimentation in feminist architectural and conceptual art practice, permit a feminist rewriting of remedial, body-bound interventions on the ageing body, opening up a critical and creative public space of communication (and action) around the (marginalized) subject of ageing, differently.